Prognosis of Patients Over 60 Years Old With Early Rectal Cancer Undergoing Transanal Endoscopic Microsurgery – A Single-Center Experience - Zhang, Mingqing; Zhang, Yongdan; Jing, Haoren; Zhao, Lizhong; Xu, Mingyue; Xu, Hui; Zhu, Siwei; Zhang, Xipeng (Frontiers in Oncology, 2022)
AIM: Transanal endoscopic microsurgery (TEM) is widely performed in early rectal cancer. This technique offers greater organ preservation and decreases the risk of subsequent surgery. However, postoperative local recurrence and distant metastasis remain challenges for patients with high-risk pathological factors. This single-center study reports the prognosis of early rectal cancer patients over 60 years old after TEM. Methods: The data of the patients over 60 years old who underwent local anal resection were collected retrospectively. Moreover, the 5-year follow-up data were analyzed to determine the 5-year DFS and OS. Results: 47 early rectal cancer patients over 60 years old underwent TEM. There were 27 patients with high-risk factors and 20 patients without high-risk factors. Two patients underwent radical surgery after TEM and ten patients received adjuvant treatment. Local recurrence occurred in 7 patients, of which 4 underwent salvage surgery. The 5-year progression-free survival rate was 75.6%, which was lower in the high-risk patients group (69.6%) than in the non-high-risk patients group (83.3%) (P＞0.05). The 5-year OS was 90.2%, but there was no statistically significant difference between the two groups (high-risk patients 87.0%, non-high-risk patients 94.4%). Furthermore, there was no significant difference in DFS and OS between people over and under 70 years old. Conclusion: Some high-risk factor patients over 60 years old do not have inferior 5-year DFS and OS to the non-high-risk patients. TEM is an option for old patients with high surgical risks. Even if postoperative pathology revealed high-risk factors, timely surgical treatment after local recurrence would be beneficial to improve the 5-year DFS and OS.